Efektivitas Metode Mimicry Memorization dalam Peningkatan Penguasaan Kosa Kata Bahasa Arab Kelas IV MI Qurata A’yun Selman Tahun 2021/2022 - Rusmalia; Muhammad Hamdani (Mahira: Journal of Arabic Studies & Teaching, 2024)
The Effectiveness of the Mimicry-Memorization Method in Improving Arabic Vocabulary Mastery in Class IV MI Qurrota A’yun Sleman Academic year 2021/2022. Thesis, Yogyakarta: Faculty of Tarbiyah and Teacher Training Sciences, Sunan Kalijaga State Islamic University, 2022. This study aims to find out hoe the effectiveness of the mimicry-memorization (mim-mem) method is in increasing students’ mastery of Arabic vocabulary in order to facilitate students’ understanding and mastery of vocabulary Arabic learning. This research is a descriptive quantitative research at Madrasah Ibtidaiyah Qorrota A’yun Sleman. For the type of research itself, namely experimental research. As for the data collection method used is the test method, observation, documentation. While the data analysis in this study used SPSS 20 with data analysis techniques, namely using ‘t’ test analysis or different test. The results of this study indicate that after being carried out and seen from the result of observations and strengthened by the results of tests that have been carried out in both classes namely class IV B as the experimental class and class students achieved and average score 70,77%, wich was included in the effective category, then in the control clas, the average value obtained was 57,31%, so it was in the less effective category.